Esophageal achalasia in a two-year-old boy - Savić Đorđe; Miličković Maja; Ilić Predrag; Vukadin Miroslav; Stojakov Dejan (Srpski Arhiv za Celokupno Lekarstvo, 2020)
Introduction. Esophageal achalasia is a neurodegenerative motility disorder, which is characterized by ineffective or absent esophageal peristalsis and the lack of hypertonic lower esophageal sphincter relaxation. Achalasia causes failure to thrive in children and can have serious respiratory complications. Achalasia is a very rare condition in pediatric population, and usually misdiagnosed as gastroesophageal reflux. The treatment of choice is Heller esophagocardiomyotomy. The aim of this paper is to present a rare case of a two-year-old child with achalasia, diagnostic procedures, and successful operative treatment. Case outline. The patient´s problems started at the age of six months, with audible breathing and respiratory stridor. The child was admitted at a local hospital at seven months of age, dismissed with dietary advices, again admitted at the age of 19 months, and transferred to our institution. Upper gastrointestinal series and computed tomography revealed findings characteristic for achalasia, and on esophagoscopy exam there was no opening of lower esophageal sphincter and cardia on insufflation. Pneumatic dilation was performed with temporary improvement. Laparotomic Heller esophagocardiomyotomy with Dor partial fundoplication was successfully performed. Conclusion. Achalasia is a very rare condition in infants and young children. There is often a delay when establishing the correct diagnosis. Upper gastrointestinal series and endoscopic exam are most reliable methods to detect achalasia. Pharmacological treatment, intrasphincteric injection of botulinum toxin and pneumatic dilations are not efficient methods, especially in small children. The method of choice in the treatment of achalasia is Heller esophagocardiomyotomy with partial fundoplication.